Authority records, semantic enrichment, and Wikidata - Agenjo-Bullón, Xavier; Hernández-Carrascal, Francisca (Anuario ThinkEPI, 2018)
This article describes the processes carried out by archives, libraries, and museums to semantically enrich authority records with the aim of improving their usability while building new functionalities for search and retrieval. The tasks that are usually included within the term semantic enrichment are: data cleaning, data reconciliation to external linked open data resources, extraction of additional data, and data publication. However, reconciliation and enrichment of large volumes of data can only be done by automatic means; for example, the semantic enrichment of polymath authority records by the Spanish Polymath Virtual Library. Finally, we analyze the role that Wikidata has as one of the most widely used linked open data resources and authority file for all Wikimedia projects.
Keywords: Authority control; Semantic enrichment; Data reconciliation; Authority records; Linked open data (LOD).